Microclimatic study of the space between buildings. Case: Urban housing developments, Maracaibo (Venezuela) - Gómez, Nersa; Ferrer, Mercedes (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The paper presents the results of an investigation on environmental variables that impact the space ”“between buildings”“ in urban housing developments (UHD), in Maracaibo (Venezuela). The methodology was structured in three phases: 1. Study case selection (UHD); 2. Identification of the environmental variables that impact the quality of the built environment, in a hot and humid climate and, 3. Analysis-evaluation of environmental conditions of UHD, through the interaction of the variables ”“climate, urban morphology”“ with user”™s activities and perceptions. Different instruments were applied, observation, registration and measurement of temperature, humidity, ventilation and vegetation as well as users and residents interviews. The resulting values were correlated with the Local Comfort Model and users”™ data to determine the comfort levels. The paper concludes pointing out high levels of thermal affectation in the studied space ”“beyond the comfort band”“ that affects its usage by the residents.